2009
DOI: 10.1111/j.1447-0594.2008.00493.x
|View full text |Cite
|
Sign up to set email alerts
|

Case of membranoproliferative glomerulonephritis due to essential cryoglobulinemia without hepatitis C virus infection

Abstract: An 81-year-old man was admitted to our hospital because of leg edema. Serological studies for anti-neutrophil cytoplasmic antibody (ANCA), anti-double stranded DNA antibodies, and antibodies to hepatitis C and B were negative. Severe hypocomplementemia was present and a cryoglobulin was detected with serum immunoelectrophoresis being positive for the immunoglobulin (Ig)M kappa type. The cryoglobulin was characterized by immunoelectrophoresis which showed that the protein was composed of polyclonal IgG and kapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
(30 reference statements)
1
2
0
1
Order By: Relevance
“…Table 2 shows the published cases with cryoglobulinemic MPGN but without HCV infection in the literature, which just 4 cases have been reported. Our case was similar to the one reported by Okura et al, [ 15 ] who both had favorable response after steroid therapy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Table 2 shows the published cases with cryoglobulinemic MPGN but without HCV infection in the literature, which just 4 cases have been reported. Our case was similar to the one reported by Okura et al, [ 15 ] who both had favorable response after steroid therapy.…”
Section: Discussionsupporting
confidence: 91%
“…Two patients showed type I cryoglobulin, and 1 patient showed type II cryoglobulin. Moreover, Okura et al [ 15 ] had reported 81-year-old male with mixed cryoglobulinemic MPGN without HCV infection, who led a favorable outcome after a steroid therapy. Table 2 shows the published cases with cryoglobulinemic MPGN but without HCV infection in the literature, which just 4 cases have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 summarizes a review of the literature of the noninfectious mixed (type II) cryoglobulinemic glomerulonephritis, in which the association with serum monoclonal gammopathy was determined. 9,[13][14][15][16][17][18] Interestingly, all of the cases of the noninfectious mixed cryoglobulinemia with positive serum monoclonal gammopathy were linked with serum IgM kappa monoclonal antibody. We speculated that the IgM monoclonal gammopathy might have high autoantibody activity that allows for the formation of an immune complex, as also observed in Waldenström macroglobulinemia.…”
Section: Discussionmentioning
confidence: 99%
“…Il nostro caso clinico presenta molte analogie con quanto descritto da autori olandesi nel 2007 e da autori giapponesi e francesi *associato a esacerbazione di crioglobulinemia nel 2009: in particolare, un paziente di 81 anni con glomerulonefrite membranoproliferativa [12], sette [13] e dieci casi con altrettanta sindrome nefrosica [14], tutti senza evidenza di HCV. Pur con il limite della mancata tipizzazzione del criocrito, abbiamo formulato l'ipotesi diagnostica di sindrome crioglobulinemica, con associata nefropatia nefrosica, da verosimile crioglobulinemia mista di tipo "essenziale" (EMC).…”
Section: Discussioneunclassified